The impact of the student population growth on the academic planning in the Foreign Language Department Majors, in the period 2010-2011 - Méndez García, Marcia Jazmín
The purpose of this study was to explore, diagnose, compare and analyze the emerging impact of student population growth on the Academic Planning in the FLD majors. This research was exploratory and comparative since it related information and data from the FLD majors applying the existing literature, due to the fact that there were previous studies on this phenomenon. These studies, however, were scattered across various streams of research and thus it needed to be gathered and elaborated in such a form that it could be applied in The analysis of the studied phenomenon.